AB0698 Latent tuberculosis: a potential extrinsic factor for IGG4-related disease. (23rd January 2014) - Kawano, M.; Mizushima, I.; Yamada, K.; Fujii, H.; Matsumura, M.
Abstract : Background: IgG4-related disease (IgG4-RD) is an inflammatory systemic disease, whose lachrymal and salivary gland involvement is known as Mikulicz's disease and resembles that of primary Sjogren's syndrome (pSS) 1) . In IgG4-RD, increased Th2 and regulatory immune reactions have been shown to be involved in the pathogenesis 2) . Although the etiology of IgG4-RD is still unknown, several reports indicate some link between IgG4-RD and latent tuberculosis (TB) infection 3, 4) . Objectives: To evaluate this possible link between IgG4-RD and TB. Methods: 18 patients with IgG4-RD (Mikulicz's disease 15, autoimmune pancreatitis 2, IgG4-related kidney disease 1) and 21 patients with pSS were included in this study. We compared the results of QuantiFERON TB-2G (QFT-2G) test, past history of TB disease, history of past contact with TB, serum immunoglobulin concentrations, and eosinophil count in IgG4-RD and pSS groups. Next, eosinophil count, serum IgG levels, serum IgG4 levels, serum IgE levels, allergic predisposition, and peripheral blood mononuclear cell (PBMC) cytokine mRNA production in response to stimulation with ESAT-6 and CFP-10 between QFT-2G (+) and QFT-2G (-) group with IgG4-RD were compared. Results: 8 patients with IgG4-RD (44%) were QuantiFERON TB 2G-positive. In contrast, none of the pSS patients was QFT-2G positive, with this difference statistically significant (p=0.0007). Eosinophil count was significantly higher in IgG4-RD group (335/mm 3 ) than pSS group (75/mm 3 ). Between QFT-2G (+) and QFT-2G (-) group with IgG4-RD, serum IgE levels were significantly higher in QFT-2G (-) group than in QFT-2G (+) group (1465 U/ml versus 393 U/ml, p=0.027), and past history of TB was observed only in QFT-2G (+) group (63% versus 0%, p=0.016). PBMC IFN-γ and IL-4 mRNA production in response to stimulation with ESAT-6 and CFP-10 was significantly increased in QFT-2G (+) patients with IgG4-RD (n=8) than in QFT-2G (-) patients with IgG4-RD (n=4) (58.5 versus 5.4, p=0, 027, 9.4 versus 0.24, p=0.014, respectively). In contrast, PBMC IL-6, IL-10, and TGF-β mRNA production in response to stimulation with TB related antigens were not different between the groups. Conclusions: A relatively high percentage of IgG4-RD patients had persistent memory against tuberculosis, and Th2-mediated immune response to TB seems to be augmented in addition to Th1-mediated immune response in these patients. References: Yamamoto M, Ohara M, Suzuki C, et al. Elevated IgG4 concentrations in serum of patients with Mikulicz's disease. Scand J Rheumatol. 2004;33:432-3. Zen Y, Fujii T, Harada K, et al. Th2 and regulatory immune reactions are increased in immunoglobin G4-related sclerosing pancreatitis and cholangitis. Hepatology. 2007; 45: 1538-46. Kawano M, Yamada K, Kakuchi Y, et al. A case of immunoglobulin G4-related chronic sclerosing sialadenitis and dacryoadenitis associated with tuberculosis. Mod Rheumatol 2009; 19, 87-90. Imai T, Yumura W, Takemoto F et al. A case of IgG4-related tubulointerstitial nephritis with left hydronephrosis after a remission of urinary tract tuberculosis. Rheumatol Int 2012[Epub ahead of print]. Disclosure of Interest: None Declared